Prajnaparamita in Tibetan buddhism - Obermiller, E. (New Delhi : Paljor Publications, 1998)
Analysis of a canonical tantric work belonging to "Perfection of Wisdom" texts.
Keywords: Literature; Sanskrit- Tibetan